Decentralisation: extension of agro-climatic regional planning to the district level - Singh, Har Swarup
After tracing the history of decentralised planning the author attributes the failure in its implementation to (a) inadequate plan funds at the district level, (b) lack of recognition of local resource endowments, (c) poor technical competence, (d) lack of participatory planning and (e) absence of organic linkages. "It is in the context of the technical content of the plan and the need to develop resource-based solutions in the light of infrastructural/institutional parameters that agro-climate regional planning (ACRP) has something to offer. The merit of this approach was seen at the sub-regional level-consisting of a group of districts - more or less homogeneous in terms of soil, topography, climate and wat
Keywords: Community Development; Ashok Mehta Committee; Regional Planning - India; Agro-Climate Regional Planning (ACRP); Decentralisation - India